The Seven Selves of Dementia - Bomilcar, Iris; Bertrand, Elodie; Morris, Robin G.; Mograbi, Daniel C. (Frontiers in Psychiatry, 2021)
The self is a complex and multifaceted phenomenon, encompassing a variety of cognitive processes and psychosocial influences. Considering this, there is a multiplicity of ‘selves,’ the current review suggesting that seven fundamental self-processes can be identified that further our understanding of the experience of dementia. These include: (1) an embodied self, manifest as corporeal awareness; (2) an agentic self, related to being an agent and influencing life circumstances; (3) an implicit self, linked to non-conscious self-processing; (4) a critical self, which defines the core of self-identity; (5) a surrogate self, based on third-person perspective information; (6) an extended self, including external objects or existences that are incorporated into the self; and, finally, (7) an emergent self, a property of the self-processes that give rise to the sense of a unified self. These are discussed in relation to self-awareness and their use in making sense of the experience of dementia.